Injury status among secondary school rugby players / Muhamad Fakhrul Hakim Azis - Azis, Muhamad Fakhrul Hakim (Faculty of Sport Science and Recreation, 2016)
The purpose of this study is to investigate the overall injury status among secondary school rugby players in Malaysia. There were 150 rugby players aged between 13-18 years old who were selected and they were categorized based on their playing positions in rugby namely forward (n=75) and backline position (n=75). The specific aims of this study are to determine the frequency the nature of injury among forward and backline positions, to report the common incidence sites of injury and the aetiology of injury among secondary school rugby players in Malaysia and Chi-Square Test has been utilized to interpret the data in order to meet the objectives of this study. The results showed there is no association (p>O.05) on frequency of nature of injury based on playing position. Meanwhile, the region with highest injury rate from this finding was lower body with the value of 84.7% (n=127) and for the mechanism of injury, there were significantly more injuries occurred in youth rugby player during contact 96.7% (n=145) compared with noncontact 64.7% (n=97) and climate 9.3% (n=14).